Antecedents of Intrinsic Motivation, Metacognition and Their Effects on Students Academic Performance in Fundamental Knowledge for Matriculation Courses - Ibrahim, Mikail; Baharun, Hazleena; Harun, Haliza; Othman, Normah (Universiti Utara Malaysia Press, 2017)
Purpose - This study examined the interrelationships between a set of antecedent academic intrinsic motivations and metacognitive strategy such as goal orientation, perceived value and religiosity in Fundamental Knowledge for Matriculation courses (FKM). It also investigated the relationship between intrinsic motivation and metacognitive strategy on one hand, and students' academic performance on the other.